1998
DOI: 10.1016/s0014-5793(98)00991-0
|View full text |Cite
|
Sign up to set email alerts
|

An AP‐1 site in the promoter of the human IL‐5Rα gene is necessary for promoter activity in eosinophilic HL60 cells

Abstract: Interleukin-5 (IL-5) plays a crucial role in the proliferation, differentiation and activation of eosinophils. The IL-5 receptor is composed of an IL-5-specific K K subunit, which is expressed by eosinophils and basophils, and a L Lc-subunit shared with the receptors for IL-3 and GM-CSF. We identified an AP-1 element which is important for IL-5RK K promoter activity in eosinophilic HL60 cells. The AP-1 site and the previously identified EOS1 site cooperate, since single mutation of either of the sites decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
(43 reference statements)
1
6
0
Order By: Relevance
“…Although the IL-5 receptor has been documented to be expressed in dif-HC15 as determined by mRNA analyses and by ligand binding experiments, the surface expression of the receptors for IL-5 family members has not been reported (5658). Because we are interested in the priming mechanisms involved with IL-5 family members, we evaluated the expression profile of the receptors for all three family members in the naïve and dif-HC15 cells in comparison to that in human primary blood eosinophils utilizing PE/FITC-conjugated antibodies targeting the specific α subunit of each IL-5 family receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Although the IL-5 receptor has been documented to be expressed in dif-HC15 as determined by mRNA analyses and by ligand binding experiments, the surface expression of the receptors for IL-5 family members has not been reported (5658). Because we are interested in the priming mechanisms involved with IL-5 family members, we evaluated the expression profile of the receptors for all three family members in the naïve and dif-HC15 cells in comparison to that in human primary blood eosinophils utilizing PE/FITC-conjugated antibodies targeting the specific α subunit of each IL-5 family receptor.…”
Section: Resultsmentioning
confidence: 99%
“…For CaMKIV it has been suggested that it can phosphorylate CREB in vivo because it shows nuclear localization. 52 Although a role for CREB in myeloid cells has been proposed in mediating cytokine or chemokine effector functions, [53][54][55][56] it remains to be determined if CREB and CREM are physiologic substrates for CKLiK in human granulocytes. Indeed we were able to demonstrate CREB phosphorylation by IL-8 in human PMNs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Two days after transfection cells were harvested for CAT assays. CAT assays were performed as described previously [34]. CMV-LacZ co-transfection and ␤-galactosidase assays were used to correct for variations in transfection efficiency.…”
Section: Transient Transfection and Cat Assaymentioning
confidence: 99%